Espécies de THIELAVIOPSIS em palmeiras selvagens e cultivada - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
In order to contribute to the knowledge of phytopathogenic fungi that are associated with wild and cultivated palm trees that host these organisms, it is worth highlighting species or phylogenetic lineages of fungi belonging to the Ceratocystiaceae family, where they cause diseases in palm trees. The fungi that induce fruit rot and resinosis in palm trees comprise the species of the Thielaviopsis paradoxa complex. This research aims to elucidate which Thielaviopsis species are associated with native palm species and if these species are pathogenic in cultivated species. Two chapters resulted from this research. In chapter I, samples of fruits from native palm trees with symptoms of rot were collected in the states of Pará and Piauí. Thielaviopsis isolates obtained from four distinct species of Arecaceae were characterized using the concept of morphological and phylogenetic species. From the analysis, the isolates were identified as Thielaviopsis ethacetica and Thielaviopsis cerberus. All isolates induced symptoms of black rot in Cocos nucifera, Ananas comosus, and Saccharum oficcinarum stalks. In chapter II, peach palm fruits showing symptoms of black rot were collected in markets and in an experimental area in the cities of the states of Pará and Acre, Brazil, in the years 2018-2019. The fruits showed symptoms of black rot with the formation of black mycelium on the fruits. Microscopic analysis revealed the presence of typical conidia of the genus Thielaviopsis sp. With monosporic cultures were obtained and nine isolated. Based on phylogenetic analysis of the ITS and TEF-1 α gene regions, the fungi were identified as Thielaviopsis ethacetica. All isolates induced symptoms of black rot in peach palm fruits of the yellow and red varieties. This is the first record of T. ethacetica causing black rot in peach palm fruits in Brazil.
Keywords: Ceratocystidaceae; Análise filogenética; Bactris gassipaes; Complexo Thielaviopsis paradoxa; Podridão pós-colheita; CNPQ::CIÊNCIAS BIOLÓGICAS